2006
DOI: 10.1093/cercor/bhj141
|View full text |Cite
|
Sign up to set email alerts
|

The Compassionate Brain: Humans Detect Intensity of Pain from Another's Face

Abstract: Understanding another person's experience draws on "mirroring systems," brain circuitries shared by the subject's own actions/feelings and by similar states observed in others. Lately, also the experience of pain has been shown to activate partly the same brain areas in the subjects' own and in the observer's brain. Recent studies show remarkable overlap between brain areas activated when a subject undergoes painful sensory stimulation and when he/she observes others suffering from pain. Using functional magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
273
7
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(319 citation statements)
references
References 54 publications
26
273
7
7
Order By: Relevance
“…The first published report of an functional Magnetic Resonance Imaging (fMRI) experiment comparing actual pain and the perception of pain in others showed that part of the anterior cingulated cortex (ACC), the anterior insula, cerebellum and brainstem were activated both when participants experienced a painful stimulus, as well as when they observed a signal indicating that their partner was receiving a similar stimulus (Singer et al, 2004). Subsequent studies with fMRI have confirmed that parts of the pain matrix associated with the affective component of pain (mainly ACC and anterior insula) were activated by the observation of bodily pain (Jackson, Meltzoff, & Decety, 2005;Morrison, Lloyd, di Pellegrino, & Robets, 2004), the observation of facial expressions of pain (Botvinick et al, 2005;Saarela et al, 2007;Simon, Craig, Miltner, & Rainville, 2006), and even when hearing pain-related words (Osaka, Osaka, Morishita, Kondo, & Fukuyama, 2004). These initial studies, however, failed to show consistent changes within the regions known to be associated with the sensory component of pain, notably the somatosensory cortices.…”
Section: Decoding and Neurophysiological Reactions To Pain In Others mentioning
confidence: 99%
“…The first published report of an functional Magnetic Resonance Imaging (fMRI) experiment comparing actual pain and the perception of pain in others showed that part of the anterior cingulated cortex (ACC), the anterior insula, cerebellum and brainstem were activated both when participants experienced a painful stimulus, as well as when they observed a signal indicating that their partner was receiving a similar stimulus (Singer et al, 2004). Subsequent studies with fMRI have confirmed that parts of the pain matrix associated with the affective component of pain (mainly ACC and anterior insula) were activated by the observation of bodily pain (Jackson, Meltzoff, & Decety, 2005;Morrison, Lloyd, di Pellegrino, & Robets, 2004), the observation of facial expressions of pain (Botvinick et al, 2005;Saarela et al, 2007;Simon, Craig, Miltner, & Rainville, 2006), and even when hearing pain-related words (Osaka, Osaka, Morishita, Kondo, & Fukuyama, 2004). These initial studies, however, failed to show consistent changes within the regions known to be associated with the sensory component of pain, notably the somatosensory cortices.…”
Section: Decoding and Neurophysiological Reactions To Pain In Others mentioning
confidence: 99%
“…Some studies showed that only the affective component of the pain matrix are involved in empathy for pain, and thus that only emotional, not sensory, representations of pain are shared between self and others (Saarela et al, 2007;Singer et al, 2004). On the other hand, previous transcranial magnetic stimulation studies (Avenanti et al, 2005;Avenanti et al, 2006) and somatosensory evoked potential studies (Bufalari, Aprile, Avenanti, Di Russo, & Aglioti, 2007) highlighted the possible sensorimotor aspect of empathy for pain.…”
Section: Brain Responses To Sounds Of Pain and Sufferingmentioning
confidence: 99%
“…Several studies have shown that the perception of pain in others activates only the affective components of the pain matrix, such as the anterior cingulate cortex (ACC) and insula (Botvinick et al, 2005;Saarela et al, 2007;Singer et al, 2004). For instance, in the study of Saarela et al, participants viewed emotional facial expressions of disgust or pain.…”
mentioning
confidence: 99%
“…Un sin número de investigaciones han involucrado a la corteza fronto-medial (MFC) en funciones como control y monitoreo de las acciones 12,13 , monitoreo de resultados relacionados con castigos y recompensas 14,15 , percepción subjetiva de estímulos 16,17 , y cognición social 18 . Existe evidencia creciente del rol de la MFC en el autocontrol 13 , siendo esencial en el control de la acción, de modo que sea consistente con las circunstancias y propias intenciones 12,13,19 .…”
Section: Corteza Fronto Medialunclassified